ENSURING THE EDUCATIONAL ACTIVITIES EFFECIENCY IN THE CONTEXT OF INTERNATIONALIZATION: EUROPEAN HIGHER EDUCATION AREA COUNTRIES - Mariia Debych (Borys Grinchenko Kyiv Metropolitan University, 2023)
The goal of the study is the analysis of national documents on the topic of the study, the main actors who shape the policy of internationalization at the national levels and the identification of the mechanisms used to ensure the efficiency of educational activities in universities in the context of internationalization in countries that are leaders in the number of international students. To achieve the above goal, several methods have been used, including an internet search, analysis, systematization of evident information. It was found that Ministries of education provide the regulatory framework for higher education and cooperate with other national ministries and organizations to develop international opportunities for higher education. Policies and programs to promote incoming/outgoing student mobility aimed at «degree mobility» or «credit mobility» include: grants and scholarships; simplification of visa policy; preferential admission; «Study in» marketing campaigns. The main goals of national organizations are: to maintain the visibility of higher education on the international market of educational services; attract international students to study in the country; promote language learning; join forces to solve global problems. The impact of national internationalization policies on the efficiency of educational activities is largely measured by the following quantitative indicators: number of foreign students, number of educational programs in foreign languages, and number of double degree programs. Based on the results of the analysis of European internationalization strategies, recommendations have been formulated to increase the effectiveness of educational activities in the context of internationalization.